Adaptation and validation of the Croatian version of the inventory of parent/caregiver responses to the children’s pain experience (IRPEDNA) - Neven Korda; Ivan Bućan; Ivan Kovačić; Ivan Buljan; Adriana Banožić; Jordi Miró; Livia Puljak (BMC Psychology)
Abstract Background Research has shown that parental behavior significantly influences children’s pain experiences. The Inventory of Parent/Caregiver Responses to Children’s Pain Experience (IRPEDNA) is a validated tool used to measure these reactions. Studies using the IRPEDNA have found that parental responses, shaped by cultural influences and individual perceptions, are closely linked to children’s pain coping strategies and overall distress levels. The aim of this study was to translate, culturally adapt and validate the IRPEDNA for use in the Croatian language (IRPEDNA-Cro). Methods We conducted a cross-sectional study between October and December 2012. A forward-backwards translation of the IRPEDNA from English to the Croatian language was performed according to the cross-cultural adaptation guidelines of self-report measures. The study participants were 200 parents: 100 mothers and 100 fathers from 100 families (both mother and father from the same family were included). They received IRPEDNA-Cro and Positive and Negative Affect Schedule (PANAS) questionnaires. Results The three subscales of IRPEDNA-Cro showed good reliability: Solicitousness (α = 0.81, 95% CI 0.76 to 0.85), Discouragement (α = 0.75, 95% CI 0.68 to 0.80) and Promotion of Well Being (α = 0.75, 95% CI 0.68 to 0.80). The overall scale showed high reliability in terms of both internal consistency (α = 0.83, 95% CI 0.79 to 0.87) and in association with positive PANAS was α = 0.78 (95% CI 0.72 to 0.83), while reliability for negative PANAS scale was α = 0.87 (95% CI 0.84 to 0.90). Regression analysis showed that the Discouragement scale on IRPEDNA was the best predictor of both positive and negative affect. Conclusion This article presents the translation and preliminary validation of a self-administered instrument designed to measure parents/caregivers’ responses to children’s pain behaviors in the Croatian language (IRPEDNA-Cro). The data showed that IRPEDNA-Cro provides valid and reliable information when used with Croatian-speaking adults.